A case study of space allocation and area measurements in selected medium-cost condominium units - Ferreras, Kazel U.; Quevedo Ma. Teresa (2008.)
This case study intended to find out whether selected medium-cost condominium units with different types of occupants complied with the requirements of the National Building Code of the Philippines and the House and Land Use Regulatory Board in terms of provision of living facilities, minimum floor areas, and least horizontal dimensions. It also aimed to determine whether there is a correlation between compliance to the said regulations and meeting the satisfaction of the occupant's needs. The methods used to gather data were interviews, observation, and documentation. Respondents were chosen using purposive sampling. The three respondents of the study included an executive secretary, a law student, and a housewife, who were occupants of different medium-cost condominium units in Cainta, Rizal and Makati City. Results reveal that most of the activities tend to concentrate in some areas of the units because the other areas were not functional enough to accommodate the activities that are supposed to be done there. Too many shared regular activities in one area also compromised the functionality of the space. All the subject condominium units passed the HLURB standards for minimum total floor area for a single occupancy unit as well as a family dwelling unit. While each unit can be classified as a family dwelling unit based on its total floor area, the executive secretary's unit is not appropriate for family use as it lacked certain living facilities. Majority of the areas complied with the NBC standard on minimum floor areas and least horizontal dimensions although significant limitations can be observed in the area measurements of some dining and living areas. Considering the limitations of some areas, the level of comfort and satisfaction of the respondents were quite high, which coincides with the general compliance of the units to the NBC and HLURB standards. Overall, only the law student's unit was satisfactory in accommodating her activities but this is probably because she lived alone.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Condominium spaces -- Philippines -- Rizal -- Cainta; Condominiums -- Philippines -- Makati City